2014
DOI: 10.1108/ijhcqa-02-2014-0019
|View full text |Cite
|
Sign up to set email alerts
|

Quality indicators for a consultation-liaison psychiatry service

Abstract: This CLP service was evaluated by measuring utilisation rates, referral response timeliness and consumer feedback. Referral to contact time is a useful objective quality indicator but should be combined with subjective yet standardised measures surveying service recipients (patients and referring staff) to be comprehensive and meaningful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…A systematic review from 2014 [ 10 ] which included 13 studies examining staff feedback on CLP services, showed general satisfaction levels between 21 to 100%; the majority of studies reported satisfaction rates between 56 and 86%. A study from 2014 with 41 responses and a response proportion of 59% from consultants at a general hospital [ 15 ] showed overall satisfaction with the CLP service as being at 63 to 98% of staff members. Although slightly different rating scales were used, the levels of satisfaction studied were comparable with our results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A systematic review from 2014 [ 10 ] which included 13 studies examining staff feedback on CLP services, showed general satisfaction levels between 21 to 100%; the majority of studies reported satisfaction rates between 56 and 86%. A study from 2014 with 41 responses and a response proportion of 59% from consultants at a general hospital [ 15 ] showed overall satisfaction with the CLP service as being at 63 to 98% of staff members. Although slightly different rating scales were used, the levels of satisfaction studied were comparable with our results.…”
Section: Discussionmentioning
confidence: 99%
“…There is widespread agreement among professionals, managers and policy makers that an ongoing evaluation of CLP service quality using standardized measurements [ 13 ] is needed. Different measurement tools and quality indicators have been identified and developed in recent years, to assess consultee satisfaction [ 14 ], service utilization and efficiency [ 15 ], to secure quality improvement and accreditation [ 13 ], to improve service effectiveness [ 16 ] and to facilitate quality and outcome assessment and standardization of services [ 17 ]. However, a more widespread examination of CLP service quality across different countries [ 18 ], with an emphasis on using structured measurement tools [ 16 ] is needed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To meet these needs, psychological or psychiatric consultation-liaison (CL) services within inpatient medical settings are consulted for psychiatric and cognitive assessment, evaluation for capacity, medication or behavioral interventions for mood disorders/anxiety, pain, treatment non-adherence, coping/adjustment, and behavioral/conduct concerns (Carter et al, 2003;Kitts et al, 2013). CL services have positively impacted cost-effectiveness-length of stay (LOS) and hospital readmission rates (Andreoli et al, 2003;Aoki et al, 2004;Kishi et al, 2004;Muskin et al, 2016), psychological clinical outcomes-depression, anxiety, pain intensity, quality of life (Broadbent et al, 2009a(Broadbent et al, , 2009bEhlert et al, 1999;Paterson et al, 2018), treatment adherence (Gillies et al, 2015), and patient and consulting provider satisfaction (De Albuquerque et al, 2008;Gillies et al, 2015;Kitts et al, 2013;Wood & Wand, 2014).…”
mentioning
confidence: 99%